Analysis of the effectiveness and potential of the as a learning media tool in the modern era - Ditha Puteri Noer Fauziah; Muhammad Dito Yulianto; Siti Amelia Fasha (Hipkin Journal of Educational Research, 2024)
Education is changing rapidly along with developments in science and technology. Metaverse, an interactive 3D virtual space concept, offers excellent potential as an effective learning medium. However, challenges such as lack of interaction between students and teachers and commitment to aligning technology with actual learning needs also arise. To overcome this challenge, collaboration is needed between various parties, including educational institutions, the government, the technology industry, teachers, and parents. Proper training, equitable access, careful planning, and technology security awareness are essential to integrating Metaverse into learning. The potential of Metaverse in education is enormous, especially in improving critical thinking skills, communication abilities, and the use of technology for students in the modern era. However, to utilize this potential optimally, a deep understanding is needed from teaching staff and related parties in designing and implementing metaverse-based learning. Metaverse has a significant role in advancing education and achieving a better future. The research results show that the metaverse is very useful in the continuity of education, where students play a direct active role in more creative and innovative activities; this adapts to the current curriculum and is implemented directly in the metaverse.   Abstrak Pendidikan mengalami perubahan dengan cepat seiring dengan perkembangan ilmu pengetahuan dan teknologi. Sebuah konsep ruang virtual 3D yang interaktif, menawarkan potensi besar sebagai media pembelajaran yang efektif. Namun, tantangan seperti kurangnya interaksi antara peserta didik dan pendidik serta komitmen dalam menyelaraskan teknologi dengan kebutuhan pembelajaran sebenarnya juga muncul. Untuk mengatasi tantangan ini, diperlukan kolaborasi antara berbagai pihak, termasuk lembaga pendidikan, pemerintah, industri teknologi, pendidik, dan orang tua. Pelatihan yang tepat, akses yang merata, perencanaan yang matang, dan kesadaran akan keamanan teknologi menjadi langkah penting dalam mengintegrasikan dalam pembelajaran. Potensi dalam pendidikan sangat besar, terutama dalam meningkatkan keterampilan berpikir kritis, kemampuan komunikasi, dan pemanfaatan teknologi bagi peserta didik di era modern. Namun, untuk memanfaatkan potensi ini secara optimal, diperlukan pemahaman yang mendalam dari tenaga pendidik dan pihak terkait dalam merancang dan mengimplementasikan pembelajaran berbasis .memiliki peran yang signifikan dalam memajukan pendidikan menuju masa depan yang lebih baik. Hasil dari penelitian yang dilakukan menunjukkan bahwa metaverse sangatlah berguna dalam keberlangsungan pendidikan dimana peserta didik berperan aktif secara langsung dalam kegiatan yang lebih kreatif dan inovatif, hal ini menyesuaikan bagaimana kurikulum yang ada pada saat ini dan diimplementasikan secara langsung bagaimana metaverse tersebut. Kata Kunci: era modern; media pembelajaran; Metaverse; teknologi